Durability of humoral responses after an adapted SARS-CoV-2 mRNA vaccine dose in hemodialysis patients - Benning, Louise; Bartenschlager, Marie; Kim, Heeyoung; Morath, Christian; Zeier, Martin; Schnitzler, Paul; Bartenschlager, Ralf; Speer, Claudius (Vaccines, 2024)
We recently showed that an adapted SARS-CoV-2 vaccine with wildtype and BA.4/BA.5 Omicron subtype epitopes induced a broad short-term immune response in hemodialysis patients. Antibodies with protective capacity were boosted significantly after a follow-up period of 3 weeks following a fifth vaccine dose. However, data on the longevity of the humoral response after bivalent vaccination are lacking but urgently needed to make recommendations for further booster vaccinations in this patient group. This study is an extension of our previously published data including 40 patients on hemodialysis with a follow-up period of 12 months after an adapted booster vaccine dose. We performed a detailed characterization of humoral immune responses and assessed breakthrough infections. In addition, the severity of breakthrough infections was assessed using an established grading system. Anti-S1 IgG and surrogate neutralizing antibodies significantly decreased during the period of 12 months (p < 0.01 and p < 0.001, respectively). Live-virus neutralizing antibodies against the wildtype and the BA.5 subtype also significantly decreased over time (p < 0.01 and p < 0.01, respectively). However, even 12 months after administration of the adapted vaccine dose, all 40/40 (100%) of hemodialysis patients showed detectable SARS-CoV-2 wildtype neutralization activity, with 35/40 (88%) also exhibiting detectable BA.5 subtype neutralization activity. During follow-up, 13/40 (33%) patients contracted a SARS-CoV-2 breakthrough infection, among which 12 cases were categorized as asymptomatic or mild, while only 1 case was classified as moderate disease activity. Thus, bivalent booster vaccination seems to induce a sustained immune response in hemodialysis patients over a period of 12 months with breakthrough infections occurring frequently but predominantly manifesting as asymptomatic or mild.
Gesehen am 15.01.2025